Contribution to the knowledge of the coastal vegetation of the SIC IT9110005 "Zone Umide della Capitanata" (Apulia, Italy). (4th July 2017) - Tomaselli, V.; Sciandrello, S.
Abstract: An overview of the coastal vegetation of Site of Community Importance "Zone Umide della Capitanata" (Puglia Region) is here presented. Original relevés were performed in different locations of the site. On the basis of the in-field observations (142 original relevés) and of literature data, 44 plant communities have been defined, belonging to the following classes: Lemnetea minoris, Ruppietea maritimae, Potametea pectinati, Phragmito - Magnocaricetea, Cakiletea maritimae, Ammophiletea, Helichryso-Crucianelletea maritimae, Juncetea maritimi, Sarcocornietea fruticosae, Saginetea maritimae, Thero - Suaedetea, Tuberarietea guattatae, Nerio - Tamaricetea . For each vegetation unit, the distribution area at local and regional level and the relation to habitat types of the 92/43 EEC Directive are provided.